Density of states of Dirac–Landau levels in a gapped graphene monolayer under strain gradient - Shubnyi, V.O.; Sharapov, S.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
We study a gapped graphene monolayer in a combination of uniform magnetic field and strain-induced uniform pseudomagnetic field. The presence of two fields completely removes the valley degeneracy. The resulting density of states shows a complicated behavior that can be tuned by adjusting the strength of the fields. We analyze how these features can be observed in the sublattice, valley and full density of states. The analytical expression for the valley DOS is derived.